2022
DOI: 10.1088/1741-2552/ac494f
|View full text |Cite
|
Sign up to set email alerts
|

A high-performance brain switch based on code-modulated visual evoked potentials

Abstract: Objective. Asynchronous brain-computer interfaces (BCIs) are more practical and natural compared to synchronous BCIs. A brain switch is a standard asynchronous BCI, which can automatically detect the specified change of the brain and discriminate between the control state and the idle state. The current brain switches still face challenges on relatively long reaction time (RT) and high false positive rate (FPR). Approach. In this paper, an online electroencephalography-based brain switch is designed to realize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The weights are typically determined using the empirical formula from [33]: a(m) = m − 1.25 +0.25. However, this formula may not be universally suitable, prompting some studies to perform search and optimization [38]. In this paper, we initially adopt the grid search method from [31] to optimize parameters of the filters, which starts by searching for the lower and upper limits of the basic band, and then a grid search is performed to determine the number of filters and their frequency intervals.…”
Section: Parameter Optimizationmentioning
confidence: 99%
“…The weights are typically determined using the empirical formula from [33]: a(m) = m − 1.25 +0.25. However, this formula may not be universally suitable, prompting some studies to perform search and optimization [38]. In this paper, we initially adopt the grid search method from [31] to optimize parameters of the filters, which starts by searching for the lower and upper limits of the basic band, and then a grid search is performed to determine the number of filters and their frequency intervals.…”
Section: Parameter Optimizationmentioning
confidence: 99%
“…Currently, brain switches have been successfully developed based on a few types of EEG signals, including sensorimotor rhythm [3][4][5], motor-related cortical potential [6], steady-state visual evoked potential (SSVEP) [7], P300 [8,9], code-modulated visual evoked potential (c-VEP) [10,11], and hybrid signals [12,13]. These developed prototypes demonstrate their effectiveness in wheelchair control [8,[12][13][14][15], a BCI speller [10,11], robot control [16,17], an emergency call system for amyotrophic lateral sclerosis patients [18], etc. Although these studies are quite promising, their reported performances are still substantially far from the requirement of practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a high-performance brain switch should accurately and promptly detect a subject's intention of control, which means the true positive rate (TPR) should be as high as possible. At the same time, the onset detection time or reaction time (RT) should be as short as possible [1,11]. Until a couple of years ago, even the state-of-the-art brain switches were hindered by a false positive every few minutes and detected the onset of the brain switch within a few seconds or even longer under a moderate TPR [1].…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al developed a BCI-based system to estimate drivers' drowsiness [6]. Zheng et al proposed a high-performance brain switch based on code-modulated visual evoked potentials with both fast reaction and low false positive rate (FPR) during idle state [7]. Among all BCI paradigms, Electroencephalography (EEG) is a method of acquiring brain waves that has attracted many researchers due to its high temporal resolution and noninvasive nature [8], [9].…”
Section: Introductionmentioning
confidence: 99%